2021
DOI: 10.1038/s42949-021-00030-0
|View full text |Cite
|
Sign up to set email alerts
|

Early pandemic COVID-19 case growth rates increase with city size

Abstract: The current outbreak of COVID-19 poses an unprecedented global health and economic threat to interconnected human societies. Strategies for controlling the outbreak rely on social distancing and face covering measures which largely disconnect the social network fabric of cities. We demonstrate that early in the US outbreak, COVID-19 spread faster on average in larger cities and discuss the implications of these observations, emphasizing the need for faster responses to novel infectious diseases in larger citie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Andrew J. Stier stated in their study that early pandemic COVID-19 case growth rates increase with city size and found that early in the outbreak COVID-19 spread faster in larger cities. Our data has not been limited to larger cities but rather it was taken from whole of the country where we have also found same finding about higher growth rate in early outbreak which found to be reduced with passage of time in the pandemic [17]. Sawsan et.al found about increasing number of Kawasaki-like disease in patients with COVID-19 and continued to be reported worldwide.…”
Section: Discussionsupporting
confidence: 79%
“…Andrew J. Stier stated in their study that early pandemic COVID-19 case growth rates increase with city size and found that early in the outbreak COVID-19 spread faster in larger cities. Our data has not been limited to larger cities but rather it was taken from whole of the country where we have also found same finding about higher growth rate in early outbreak which found to be reduced with passage of time in the pandemic [17]. Sawsan et.al found about increasing number of Kawasaki-like disease in patients with COVID-19 and continued to be reported worldwide.…”
Section: Discussionsupporting
confidence: 79%
“…Because multiple railways and highways connect these areas, the number of infections tended to increase speedily. In the early term COVID-19 pandemic, it was found that city size correlated with COVID-19 cases 21 . Therefore, COVID-19 countermeasures were often discussed and collaboratively implemented by the governors of the three prefectures.…”
Section: Introductionmentioning
confidence: 99%
“…Because multiple railways and highways connect these areas, the number of infections tended to increase speedily. In the early term COVID-19 pandemic, it was found that city size correlated with COVID-19 cases [17]. Therefore, COVID-19 countermeasures were often discussed and collaboratively implemented by the governors of the three prefectures.…”
Section: Purposementioning
confidence: 99%